The pathologic features of the Crohn’s disease - Göksel, Süha (Cerrahpaşa Medical Journal, 2013)
Despite that Crohn’s disease has first been published as a pathologic and clinical entity in 1932, and enormous progress has been made in understanding its pathogenesis since then, there still remain unknown aspects of its etiology. Furthermore Crohn’s disease is a heterogeneous entity with, for example, 24 phenotyping subgroups according to the Vienna classification. Hence Crohn’s disease is still a problematic area in both the clinical and pathological terms. In this review, the recent consensus reached on the pathologic findings and diagnosis of Crohn’s disease is discussed, combined with the experience of the Pathology Department of the Cerrahpasa Medical Faculty.